1986
DOI: 10.1111/j.1600-051x.1986.tb01414.x
|View full text |Cite
|
Sign up to set email alerts
|

Toothbrush age and wear as it relates to plaque control*

Abstract: An investigation was conducted to test the hypothesis that age and wear of toothbrushes do not affect plaque removal. 40 preclinical dental students between the ages of 19 and 26 years were assigned randomly to 2 groups. 1 group of 19 subjects used a toothbrush for 10 weeks while the 21 subjects in the other group were given new toothbrushes every 2 weeks for 10 weeks. A baseline of zero plaque and calculus was obtained on the first visit. On subsequent visits, 2 weeks apart, the gingival status of each group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
4
3

Year Published

1992
1992
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(76 citation statements)
references
References 14 publications
3
65
4
3
Order By: Relevance
“…Second, the current American Dental Association recommendation for toothbrush replacement is every 3 to 4 months. 26 This frequency could change the results of the present study. However, in the present study, the slurry and toothbrushes were replaced after every 3 years of simulated toothbrushing because of experimental design and time management.…”
Section: Discussionmentioning
confidence: 39%
“…Second, the current American Dental Association recommendation for toothbrush replacement is every 3 to 4 months. 26 This frequency could change the results of the present study. However, in the present study, the slurry and toothbrushes were replaced after every 3 years of simulated toothbrushing because of experimental design and time management.…”
Section: Discussionmentioning
confidence: 39%
“…The only investigation which has evaluated the effect of toothbrush renewal intervals on the efficiency of plaque control found that subjects who renewed toothbrushes every two weeks exhibited better plaque control than those who used the same brush for the 10-week period of the study. 7 To date, no studies have been published which show two-three months to be the optimal renewal period for a toothbrush. Most respondents did not recommend to their patients when toothbrushes should be renewed despite the majority feeling that patients should renew toothbrushes more often.…”
Section: O N T H S R E C O M M E N D a T Io N S F O R P A T Ie N T Smentioning
confidence: 99%
“…On the contrary, other studies concluded that there is no significant difference in plaque scores were achieved by the subjects with the highest toothbrush wear in comparison to those subjects with the lowest toothbrush wear (13, 14). However, another study has recommended that toothbrushes be replaced frequently to ensure optimal plaque control (15). …”
Section: Introductionmentioning
confidence: 99%